Penerapan Model Teams Games Tournament Berbantu Media PUBBADAR Terhadap Pemahaman Konsep Matematika - Nauha, Syifa Salsabila; Riswari, Lovika Ardana; Rondli, Wawan Shokib (Delta: Jurnal Ilmiah Pendidikan Matematika, 2025)
This research was motivated by students' low understanding of concepts. Based on the results of observations and interviews, it was found that there was a lack of variety in learning models and media as well as students' low comprehension and memory. This research aims to determine the influence of the Teams Games Tournament (TGT) model assisted by PUBBADAR media on the understanding of mathematical concepts of fifth grade students at SD 1 Getas Pejaten. The research population was all 38 class V students. This research is in the form of quantitative research using an experimental method, namely Pre-Experimental in the form of One Group Pretest Posttest Design. Data analysis took the form of a normality test and hypothesis test (Paired Sample T-Test) using the SPSS application. The normality test results produce a sig value. pretest reached 0.811 while the sig. posttest reached 0.349 which shows that the sig. pretest > 0.05 and sig value. posttest > 0.05. It can be said that the pretest posttest data is normally distributed. The results of the paired sample t-test show that there is a difference in the average pretest score, namely 57.92 and posttest 80.52. Meanwhile, the results of the paired sample t-test are 0.000 or 0.000 < 0.05. It can be said that Ho is rejected and Ha is accepted. It can be concluded that the application of the TGT model assisted by PUBBADAR media has an effect on the conceptual understanding of class V students at SD 1 Getas Pejaten.